Дослідження неперервного профілювання гвинтових стрічок - Пилипець, М. І.; Гевко, І. Б.; Лещук, Р. Я. (Видавництво Національного університету «Львівська політехніка», 2001)
The results of continuous screw belts profiling, which are widely used in mechanical engineering are presented. The effective constructional and technological parametres of the machine tools and devices profiling which are the flesis of the latest technological equipment constructions are determined.